1985
DOI: 10.1111/j.1471-4159.1985.tb08793.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood–Brain Barrier Transport of Valproic Acid

Abstract: Valproic acid distribution in brain is less than that of other anticonvulsants such as phenytoin or phenobarbital. Possible mechanisms for this decreased distribution space in brain include (a) increased plasma protein binding of valproate relative to the other anticonvulsants and (b) asymmetric blood-brain barrier (BBB) transport of valproate such that the brain-to-blood flux exceeds the blood-to-brain flux. These mechanisms are investigated in the present studies using the intracarotid injection technique in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(41 citation statements)
references
References 35 publications
0
37
1
2
Order By: Relevance
“…The lack of probenecid to increase the penetration of VPA into either extracellular fluid or brain tissue of rats is in contrast to several previous reports in which probenecid was shown to elevate brain, CSF, or brain dialysate levels. However, after our initial study in dogs (Frey and Löscher, 1978), most subsequent studies on probenecid's effects on VPA brain distribution were done in rabbits (e.g., Cornford et al, 1985;Adkison et al, 1994Adkison et al, , 1996Scism et al, 2000), so that interspecies differences could be involved in the apparent discrepancies between the present and previous studies. This possibility is also suggested by a study of Golden et al (1993), in which probenecid was shown to decrease VPA concentrations in the CSF of rats, whereas we found an increase in CSF concentrations of VPA following probenecid in dogs (Frey and Löscher, 1978).…”
Section: Valproate and Efflux Transporters 339contrasting
confidence: 54%
“…The lack of probenecid to increase the penetration of VPA into either extracellular fluid or brain tissue of rats is in contrast to several previous reports in which probenecid was shown to elevate brain, CSF, or brain dialysate levels. However, after our initial study in dogs (Frey and Löscher, 1978), most subsequent studies on probenecid's effects on VPA brain distribution were done in rabbits (e.g., Cornford et al, 1985;Adkison et al, 1994Adkison et al, , 1996Scism et al, 2000), so that interspecies differences could be involved in the apparent discrepancies between the present and previous studies. This possibility is also suggested by a study of Golden et al (1993), in which probenecid was shown to decrease VPA concentrations in the CSF of rats, whereas we found an increase in CSF concentrations of VPA following probenecid in dogs (Frey and Löscher, 1978).…”
Section: Valproate and Efflux Transporters 339contrasting
confidence: 54%
“…estrone sulfate and ochratoxin A); however, the substrate selectivity of these two families overlaps little. The transporter(s) responsible for the efflux transport, via BBB and/or BCSFB, of naphthol glucuronide, dideoxyinosine, azidodeoxythymidine, and valproic acid has not been identified (27)(28)(29)(30). The functional analysis and localization of oatp1, oatp2, and OAT3 will clarify the molecular mechanisms of the organic anion transport in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…29 There are several studies showing that an anticonvulsant, valproic acid, is efficiently transported across the BBB. 30,31 When uptake of valproic acid was measured by an in situ brain perfusion method, it was saturable, with Km values between 10 and 20 mM, depending on the measured brain regions. Uptake of valproic acid was reduced in the presence of medium-chain fatty acids such as hexanoate, octanoate, and decanoate, but not propionate or butyrate, indicating that valproic acid is taken up into the brain via a transport system for medium-chain fatty acids, not short-chain fatty acids.…”
Section: Monocarboxylate Transport Familymentioning
confidence: 99%